2009
DOI: 10.1016/j.jnoncrysol.2008.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive defects in silica layers implanted with germanium ions

Abstract: a b s t r a c tGe-implanted silica layers have been investigated by high-power pulsed synchrotron-photoluminescence (PL), photoluminescence excitation spectroscopy (PLE), and optically stimulated electron emission (OSEE) with respect to association of excitation and absorption bands to respective emission bands and lifetimes of excited defect states. In this way singlet-singlet (4.35 eV) and triplet-singlet (3.18 eV) radiative transitions from excited states of oxygen-deficient centers (ODC) in Ge-doped silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…Complex silica-based functional materials, including structures containing semiconductor quantum dots, are often created by means of ion implantation. Required compatibility with the current technology in the semiconductor industry induces an extensive research on Si-based emitting materials in which photoluminescence (PL) properties of Si-, Ge-, and Sn-implanted SiO 2 layers were studied [2][3][4]. Such ion-beam synthesis is inevitably accompanied by generation of point defects which affect the optical properties of the host matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Complex silica-based functional materials, including structures containing semiconductor quantum dots, are often created by means of ion implantation. Required compatibility with the current technology in the semiconductor industry induces an extensive research on Si-based emitting materials in which photoluminescence (PL) properties of Si-, Ge-, and Sn-implanted SiO 2 layers were studied [2][3][4]. Such ion-beam synthesis is inevitably accompanied by generation of point defects which affect the optical properties of the host matrix.…”
Section: Introductionmentioning
confidence: 99%
“…3, [5]). Thus one can see that our treatment allows discrimination of different centers with overlapped emission bands by their quenching character similar to lifetime discrimination in kinetics measurements [12].…”
Section: Resultsmentioning
confidence: 52%
“…The first explanation of noted bands is as a point defect such as an oxygen vacancy or a relaxed "SiASi" (a-ODC) and "GeAGe" (b-ODC) bonds (see, for example, [13]). Our previous investigation has shown that there could be even more types of oxygen-deficient centers contributing to 2.7-3.2 eV and 4.2-4.5 eV PL [14]. The second approach ascribes them to twofold silicon and germanium atoms respectively [6,15,16].…”
Section: Discussionmentioning
confidence: 99%